Negosiasi antara Hukum Positif dengan Hukum Islam: Penetapan Wali Nikah di Kantor Urusan Agama Idi Rayeuk, Aceh, Indonesia: Negosiasi antara Hukum Positif dengan Hukum Islam: Penetapan Wali Nikah di Kantor Urusan Agama Idi Rayeuk, Aceh, Indonesia - Fadli, Fadli; Juliandi, Budi (Institut Agama Islam Negeri (IAIN) Pontianak, 2021)
Indonesian Marriage Law stipulates that biological fathers have the right to become marriage guardians for children born less than six months of the age of marriage of their parents. The Office of Religious Affairs (KUA) Idi Rayeuk gave the guardian judge the authority to replace the biological father’s position to marry off his daughter. This article aims to determine how Indonesian Marriage Law and Islamic law were compromised and negotiated at KUA Idi Rayeuk in determining marriage guardians for children born less than six months of their parents’ marriage age. This research is normative-empirical research by using interviews and documentation collected during July-December 2019 as the data source. The results showed that the determination of guardian judges at KUA Idi Rayeuk for women born less than six months of marriage to their parents resulted from compromise and negotiation between positive law and Islamic law, especially Syafi’i fiqh. KUA Idi Rayeuk and religious leaders agreed to use Syafi’i fiqh to appoint judges’ guardians as marriage guardians for children born less than six months of their parents. marriage age. The result of these negotiations is that the marriage practice is given to the judge’s guardian following the practice of the penghulu representing the nasab guardian in marriage (representative guardian). The name of the judge’s guardian is not included in the documents related to the marriage.